Preventive effect of ipragliflozin on nocturnal hypoglycemia in patients with type 2 diabetes treated with basal‐bolus insulin therapy: An open‐label, single‐center, parallel, randomized control study. Issue 3 (25th November 2016) - Okajima, Fumitaka; Nagamine, Tomoko; Nakamura, Yuko; Hattori, Naomi; Sugihara, Hitoshi; Emoto, Naoya
Abstract: The efficacy of the administration of sodium‐glucose co‐transporter 2 inhibitor or the co‐administration of sodium‐glucose co‐transporter 2 inhibitor and dipeptidyl peptidase‐4 inhibitor to insulin therapy is not well known. A total of 58 patients with type 2 diabetes, admitted for glycemic control, were randomized to basal–bolus insulin therapy (BBT) alone or BBT plus 50 mg ipragliflozin and/or 20 mg teneligliptin. Insulin doses were adjusted to maintain normal blood glucose levels. Plasma glucose profiles were estimated by continuous glucose monitoring before discharge. Required insulin doses were not significantly different among the treatment groups. The frequency of nocturnal hypoglycemia was significantly lower in the groups treated with ipragliflozin (6.5 ± 10.6%) and ipragliflozin plus teneligliptin (6.9 ± 14.3%) than in the group treated with BBT alone (42 ± 43.6%). The administration of sodium‐glucose co‐transporter 2 inhibitor with or without dipeptidyl peptidase‐4 inhibitor prevented nocturnal hypoglycemia in type 2 diabetes patients with BBT. Abstract : The administration of ipragliflozin with or without teneligliptin reduced the incidence of nocturnal hypoglycemia in type 2 diabetic patients with basal‐bolus insulin therapy at the end of hospitalization for glycemic control.